2021
DOI: 10.1155/2021/8740157
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Liver Disease in Ethiopia with a Particular Focus on the Etiological Spectrums: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background. In Ethiopia, chronic liver disease (CLD) is the 7th leading cause of death, accounting for about 24 deaths per 100000 populations in 2019. Despite its burden, there is a lack of compiled pieces of evidence on CLD in the country. Thus, this systematic review and meta-analysis is intended to provide the pooled estimates of CLD etiologies and mortality rate in CLD patients in Ethiopia. Method. PubMed, Google Scholar, ScienceDirect, institutional repositories, national digital library, and the bibliogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This was consistent with previous findings done in different areas of the world, including Ethiopia. 51 , 52 The mechanism by which chronic HBV infection predisposes to liver cirrhosis is still enigmatic. However, in several models of HBV infection, it has been identified that liver injuries in chronic infection are considered to be associated with the activity of HBV-specific T cells, as HBV is not directly cytopathic.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous findings done in different areas of the world, including Ethiopia. 51 , 52 The mechanism by which chronic HBV infection predisposes to liver cirrhosis is still enigmatic. However, in several models of HBV infection, it has been identified that liver injuries in chronic infection are considered to be associated with the activity of HBV-specific T cells, as HBV is not directly cytopathic.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic liver disease is Ethiopia’s 7th leading cause of death 50 and Chronic hepatitis B and C infections and chronic consumption of alcoholic beverages are the principal etiologic agents of CLD. 18 , 51 , 52 Today, the number of deaths related to AIDS markedly reduced due to the launching of antiretroviral treatment (ART) programs in low and middle-income regions, such as sub-Saharan Africa, where both HBV and HIV are highly prevalent. 11 However, viral hepatitis B and C-related liver disease are common among people living with HIV and are responsible for the death of co-infected individuals due to non-AIDS causes.…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic hepatitis B, C, and alcoholism-related CLD 17 , 18 and HIV infection 19 are common in Ethiopia, no scientific study has been conducted to evaluate the prevalence of HIV and its co-infection with HBV or HCV among CLD patients in Ethiopia. Thus, we aimed to assess the prevalence of HIV and its co-infection with HBV and HCV among CLD patients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the cause is yet to be identified in 45% of the cases. 6 In Eastern Ethiopia, despite the high burden of liver cirrhosis of unknown etiology, fewer efforts have been made to explore its potential determinants. In this regard, our recent case-control study found aflatoxin B 1 (AFB 1 ) exposure as a potential missing etiologic factor of liver cirrhosis in Eastern Ethiopia, where significant cases of the disease were cryptogenic.…”
Section: Introductionmentioning
confidence: 99%